Prediction of Nocturnal Desaturation in Elderly Patients with Chronic Respiratory Disease - Abe, Tadashi; Takada, Nobukazu; Tomita, Tomoyuki (Nihon Rōnen Igakkai zasshi, 1992)
Previous reports suggest that nocturnal disorders of sleep and breathing have increased prevalence among the elderly, and episodic nocturnal oxygen desaturation (NOD) has an increased incidence in patients with chronic respiratory disease. Current Japanese criteria for home low flow oxygen therapy (LFOT), recommend LFOT for patients with daytime PaO2<55torr or with daytime PaO2≤60torr who have significant NOD. Strict adherence to these LFOT criteria requires full overnight monitoring of arterial oxygen saturation (SaO2) in all patients with daytime PaO2≤60torr. Since widespread nocturnal oximetry involves significant expenditure of time and resources, it is important among patients with chronic respiratory diseases to predict those who will have significant NOD. The aim of the present study was to formulate criteria for identification of patients who are most likely to demonstrate significant NOD based upon daytime respiratory function data. Subjects included 34 elderly patients with daytime PaO2≥55torr, who had stable severe chronic respiratory disease (15 chronic emphysema, 6 chronic bronchitis, 12 post-tuberculosis, and 1 kyphoscoliosis). Study data included medical history, assessment of dyspnea by Hugh Jones classification, and measurement of daytime, awake arterial blood gases and spirometry. Each subject underwent full overnight oximetry monitoring. The percentage of total sleep time recorded with SaO2≤85% was noted (DST85), and NOD was defined as DST85≥1%. Of the 34 patients, 11 were identified as NOD, and 23 as non-NOD patients. Duration and severity of dyspnea were not different between NOD and non-NOD patients. No non-NOD patient presented a history of acute exacerbation; 7 patients with NOD had a clear history of acute exacerbation. Mean daytime PaO2 of NOD patients was significantly (p<0.01) lower than that of non-NOD patients; 6 of 26 patients with a daytime PaO2>60torr showed NOD. Mean daytime PaCO2 and base excess of NOD patients were significantly higher than values for non-NOD patients (both p<0.01). Spirometry recorded for both NOD and non-NOD patients groups was not different. When the occurrence of a prior acute exacerbation or of daytime PaCO2>45torr were employed as predictive criteria, prediction of NOD patients was possible with a sensitivity of 81.8% and a specificity of 78.3%. We concluded that patients with a history of acute exacerbation or daytime PaCO2>45torr have an increased probability of NOD, so that full nocturnal oximetry is indicated in these patients.